The control of chemicals used in aquaculture in Europe - Costello, MJ; Grant, A; Davies, A; Cecchini, S; Papoutsoglou, S; Quigley, D; Saroglia, M (Journal of applied ichthyology, 2001)
A range of chemicals are used in European marine aquaculture and these may be categorized as disinfectants, antifoulants and medicines (includes vaccines). This article provides a review of chemicals used in aquaculture in Europe, their regulatory status, and a checklist of points considered best practice in the use (and avoidance of use) of medicines in marine aquaculture. The release of antifoulants and disinfectants into the marine environment is controlled by local and/or national waste discharge regulations that may in turn be guided by wider environmental quality objectives. The authorization of veterinary medicines, biologicals (vaccines) and pharmaceuticals (chemicals), in Europe is the subject of several EC Directives. Registration dossiers address the issues of product quality, safety and efficacy and include environmental and consumer safety where the product is destined for use in a food‐producing animal. Fish farmers, like all livestock producers, must have access to a range of properly authorized medicines to safeguard animal health and welfare. The distribution and supply of medicines must be appropriately controlled and their authorization appropriately includes environmental risk assessment to a common European Union (EU) or international standard. There is progress towards the harmonization of the authorization process within the EU and this will help to ensure the continued availability of medicines for fish. Consumer safety is addressed by the setting of maximum residue limits (MRLs) derived through toxicological risk assessment and by surveillance of food for residues of veterinary medicines. The system for the environmental risk assessment of chemicals used in aquaculture is being developed and is outlined in the present article. It is recommended that the supply and use of fish medicines is uniformly regulated in the EU and supported by appropriate codes of best practice. A number of codes of practice that include reference to the use of medicines have been produced both at a European level and in member states. It is recommended that all European marine aquaculture producers adopt a code of best practice for the use of medicinal and other chemicals their industry. Medicines are one part of an integrated package in dealing with animal health. This includes environmental conditions, nutrition and hygiene. The best practice guidelines presented here are based on the outcome of three European workshops as part of the EU MARAQUA project that involved industry, government and research scientists. They cover the avoidance and minimizing of the need to use medicines and other chemicals, to recording and monitoring their use and effectiveness (in case of resistance development), exchange of experiences within the industry, and staff training. Recommendations are also included for manufacturers of medicines and other chemicals, and for regulatory authorities. Minimizing the need to use medicines and other chemicals requires attention to a healthy source of fish stock. Staff must be appropriately trained in fish husbandry (to minimize stress), hygiene and disease recognition and treatment, including management of the farm site to keep it disease free. The latter may require single generations of fish per site to allow a fallow period during which a disease or parasite cycle is broken. These recommendations and guidelines are in accordance with the current codes of practice being developed by different sectors of the aquaculture industry in different countries. They do not necessarily involve significantly higher production costs and indeed are more likely to save costs as medicines and disease impacts are very costly to industry.